Sleep-related breathing disorders in patients with heart failure: classification, epidemiology and pathophysiology. Part I - K. S. Krupichka; M. V. Agaltsov; R. P. Myasnikov; O. M. Drapkina (Российский кардиологический журнал, 2021)
The problem of heart failure (HF) is one of the central problems in modern cardiology due to its high prevalence among the population and high mortality. In turn, sleep-related breathing disorders (SRBD) are widespread in patients with HF and are associated with both the progression of the underlying disease and a decrease in the quality of life. For the first time, periodic breathing, as one of the types of sleep breathing disorders, was described in patients with HF.Further study of the issue showed a high prevalence of other types of SRBD among patients with HF The article discusses the physiology of sleep breathing monitoring in a healthy person and the pathophysiology of SRBD. The pathogenesis of central sleep apnea and its relationship with HF are discussed in detail. In addition, the mechanisms of the adverse effect of obstructive sleep apnea and HF are highlighted.